War of Independence, dams and international arbitration: The Abbey Case (1864) - Céspedes, Rodrigo (Derecho Público Iberoamericano, 2023)
This paper analyzes a ruling on prisoners during the War of Independence and explores concepts such as wars of colonial liberation, the emerging international arbitration of the nineteenth century, asymmetric conflicts and state responsibility.